FINANCIAL PERFORMANCE ANALYSIS USING ECONOMIC VALUE ADDED AND MARKET VALUE ADDED METHOD IN PT GUDANG GARAM Tbk, PT HANJAYA MANDALA SAMPOERNA Tbk AND PT BENTOEL INTERNASIONAL INVESTAMA Tbk - Prabowo, Satriya Candra Bondan (Universitas Brawijaya, Indonesia, 2017)
The underlying concept of using the Economic Value Added (EVA) measurement method is the Management by Open Book (MBOB) which has a brief understanding of openness or transparency. The basis of the MBOB system is that the information received by employees should not only help them do the job effectively, but also to understand how to help the company as a whole in achieving its vision and mission. Using quantitative descriptive research method with research object of PT Gudang Garam Tbk, PT Hanjaya Mandala Sampoerna Tbk and PTBentoel Internasional Investama in 2011 until 2015, this research giving a description about company's financial performance. Based on the result from research known that PT Gudang Garam Tbk and PT Hanjaya Mandala Sampoerna Tbk produced positive EVA and MVA values for 5 (five) years of the research period. PT Bentoel Internasional Investama Tbk got negative EVA value during the last 4 (four) years of research. Meanwhile, the MVA value of the three companies was positive.